Place-based rural health professional pre-registration education programs: a scoping review - Fuller, Lara; Beattie, Jessica; McGrail, Matthew R.; Versace, Vincent L.; Rogers, Gary D. (Frontiers in Medicine, 2025)
IntroductionWith an increasing focus on social accountability in program design in response to a shortage of rural healthcare professionals, emerging approaches in pre-registration health professional education (HPE) offer ‘place-based’ solutions. This review assesses the adoption of these approaches by the international HPE community and describes how programs are designed to recruit and train students ‘in place’.MethodsUtilizing a global scoping review, a search strategy of relevant HPE databases was developed based on the review’s eligibility criteria and key search terms. Titles and abstracts of all articles were screened against the review’s inclusion criteria, followed by full text review of articles retained. Reporting followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for scoping reviews (PRISMA-ScR) checklist.ResultsDatabase searches identified 4,215 articles (1,526 duplicates). Title and abstract screening were completed, with 319 retained for full text review. Of these, 138 met the inclusion criteria, with 50 unique HPE programs from 12 countries identified, predominantly from medicine or nursing and midwifery. Programs often had a dual purpose to provide a rural workforce and increase access to HPE for under-represented groups. Recruitment strategies included preferential admission of local students, identifying students with rural or primary care intentions, community involvement in selection, and pre-entry programs. A typology of four training models was identified: short-term rural placements, extended rural placements, rural campuses, and distributed blended learning. Distributed blended learning occurred primarily in nursing and midwifery programs, enabling students to train in their home rural communities. Outcomes evaluated by programs focussed on graduates’ work locations, the effectiveness of widening access measures, and academic results.DiscussionDespite heterogeneity of design and context, place-based programs were characterized by three common features closely aligned with social accountability: widening access to HPE, comprehensive program design and a community-engaged approach. Key considerations for place-based HPE program design are the geographical scale of the program, strategies for student recruitment from the target region, provision of continuity with rural communities through longitudinal training experiences, engaging communities in the design and delivery of the program, and alignment of evaluation with the goals of the program and the communities served.